TRIATHLON : Expert training and race advice for beginners and improvers - Bliss, Dominic; Bates, Dawn; Bye, Jason (London : Dog 'n' Bone Books, an imprint of Ryland Peters & Small Ltd, 2018)
Are you up to the challenge of the triathlon, one of the ultimate tests of human fitness, endurance, and conditioning? With three elements - swimming, cycling, and running - it pushes your body's limits in ways that very few other sports can and the buzz you get from finishing is addictive. Here, sports journalist and triathlete Dominic Bliss explains what it is about this event that captures the imagination and how anybody with just a modicum of fitness can train to complete this celebrated feat of grit and determination. Starting with the Basics, Dominic goes into the history of the sport and discusses what it takes to compete in a race. Next is Training, where everything you need to know to prepare for the big event is outlined. Included are training plans for several distances to help not only first timers, but also those looking to improve their times. There's professional advice on diet, improving your swimming technique, staying aerodynamic on the bike, and much more. The Equipment section follows, providing practical advice on exactly what you need in order to race.
The basics -- Swim training -- Bike training -- Run training -- Transition training -- Training schedules -- Race day -- The world's greatest triathlons.
Includes index.
Keywords: Triathlon; Triathlon -- Training